Radio-echo sounding reflectivity data at a subglacial trough system of Isunnguata Sermia, West Greenland, April 2011 - Pettersson, Rickard (Uppsala University, 2023)
The data Two-way travel-time to and reflectivity of the subglacial bondary at a small subglacial trough at Issungata Isunnguata Sermia, West Greenland.

The data is a plain text file with comma separated columns in the order: ID, X,Y,Z, TWTT, R, where:

ID: Unique identifier for each recordX,Y,Z: Geographical position of the record in UTM 22 (WGS-84) projectionTWTT: Two-way travel-time for the radarsignal to the subglacial reflection given in nano seconds.R: Relative reflectivity of the subglacial reflection in dB.

The dataset was originally published in DiVA and moved to SND in 2024.
Radio-echo sounding reflectivity data at a subglacial trough system of Isunnguata Sermia, West Greenland, April 2011
Keywords: Greenland; Greenland; subglacial; subglacial; Earth Science with specialization in Physical Geography; Earth Science with specialization in Physical Geography; reflectivity; reflectivity; radio-echo sounding; radio-echo sounding; Geophysics; Geofysik; Physical Geography; Naturgeografi